Comparative study between vasectomy and epididymectomy for preparation of teaser Ram: Al-Dahhan,M.R.A.Amen,A.A.and Al-Badry,K.I - Al-Dahhan, M. R.A. (The Iraqi Journal of Veterinary Medicine, 2008)
Teaser rams were used for discovering estrus in ewes because this techniqueis very important for super ovulation,embryo transfer and transgenic animalsprograms.sever techniques were used for preparation of teaser animalsespecially in sheeps so this study was designed to compare between twosurgical methods (vasectomy and epididymectomy).Six Assaf of breed rams,Clinical reproduction system,libido and laboratoryexamination (volume ejaculate,mass and individual motility and spermconcentration). were performed 2 week before experiment for qualificationof the general health of the animals the animals were divided into two equalgroups, Vasectomy in the first group and epididymectomy in theanother.Cases were followed up clinically, laboratory examination andhistological.Results showed that surgery of epididymectomy takes longer time thanvasectomy.Vasectomiesed animals showed sever pain during first tow dayswith simple adhesion in the site of operation, while epididymectomy causedsever adhesion between the testis and skin with odema in the site ofoperation also the pain was sever in addition to, it takes longer time than invasectomy. The seminal fluid examination showed disappear of life spermsimmediately after operation vasectomy or epididymectomy also histologicalchanges were obtained in both types of surgical methods ,which includereduce in the rate of spermatogenisis, thickness of basement membren,whilethese changes were more sever after vasectomy.Results of this study was showed that epididymectomy technique shouldsuperior results than vasectomy for longer time.